Efficacy of high-dose steroids versus low-dose steroids in the treatment of immune checkpoint inhibitor-associated myocarditis: a case series and systematic review - Man, Xiuyue; Wang, Hong; Chen, Chen; Cong, Xiaofeng; Sun, Lemeng; Sun, Xueru; Chen, Chen; Zhang, Jing; Yang, Lei (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitor-associated myocarditis (ICI-M) is a rare yet potentially fatal complication of immunotherapy, with no standardized treatment protocol due to limited data. The use of varying steroid doses has resulted in inconsistent outcomes.MethodsWe retrospectively identified patients diagnosed with ICI-M at our institution between January 2020 and February 2024. Additionally, we conducted a comprehensive literature review using PubMed, Embase, and the Cochrane Library to facilitate a comparative analysis of clinical responses. The primary aim was to compare clinical outcomes and therapeutic responses between patients treated with high-dose versus low-dose methylprednisolone.ResultsPatients receiving an initial high-dose intravenous methylprednisolone (1 g/day) exhibited a more rapid reduction in myocardial injury markers, including troponin I/T (cTnI/T), creatine kinase (CK), and N-terminal pro b-type natriuretic peptide (NT-proBNP), compared to those receiving lower doses. This group also demonstrated lower incidences of biomarker rebound and maintained lower levels over time. Additionally, the clinical treatment process was more straightforward in the high-dose group, with treatment efficacy surpassing that observed in patients who received an initial methylprednisolone (mPSL) dose of less than 1 g/day. Regarding prognosis, the incidence of major adverse cardiovascular events (MACE) and cardiovascular mortality was significantly lower in the high-dose group compared to the low-dose group.ConclusionsIn patients with immune checkpoint inhibitor-associated myocarditis, the prompt administration of high-dose corticosteroid pulse therapy (1 g/day) is strongly associated with improved clinical outcomes. This intervention rapidly lowers myocardial injury biomarkers (cTnI/T, CK, NT-proBNP) while minimizing the risk of biomarker rebound, thus optimizing clinical management. Notably, it significantly reduces the incidence of major adverse cardiovascular events (MACE), thereby enhancing patient prognosis. The duration of therapy should be tailored based on clinical response. In cases of steroid resistance, combination therapies may provide additional benefit.